Review on various modelling techniques for the solar dryers. (September 2016) - Prakash, Om; Laguri, Vinod; Pandey, Anukul; Kumar, Anil; Kumar, Arbind
Abstract: This review paper is focused on the various modelling techniques for the solar dryer system. The modelling techniques are very important to develop, increase drying efficiency, analyse and predict the performance of different kinds of solar drying system. The modelling techniques are also important for predicting the temperature of crop moisture content, drying rate, quality of crop and colour of crops. Computational fluid dynamics (CFD can be applied for analysing and investigating of air flow and spry of temperature in the drying system. Adaptive-network-based fuzzy inference system (ANFIS) can be used to predict the behaviour of the solar drying system. ANN is used to calculate the mass of the dried crops on hourly basis. FUZZY is very important software for using the simulation of drying system. That can also be used to accurately predict the results with a minimum error. The mathematical modelling techniques are used for testing the drying behaviour of crops in the laboratory. It act in effect tool between scientists and investigators. It helps short of spending vast amount of time, energy and money in experimental events. Before fabrication the modelling techniques are very supportive in simulation of different types of solar drying system. Thus, analysis on the base of modelling techniques is not only save time but also save the capital investment in solar drying system. The advantage and future scope of modelling techniques is also discussed.